A study of the United Arab Emirates legislature under the 1971 Constitution : with special reference to the Federal National Council (FNC) - Al-Rokn, Mohammed Abdulla Mohammed (1991)
This study Is concerned with the Federal National Council (FNC) in the United Arab Emirates (U.A.E.) under the 1971 Constitution. In selecting the U.A.E. as a case study, a historical and socioeconomic perspective is adopted. The thesis analyses the U.A.E. traditional society and the effect of external factor namely its relation with Britain, and internal factor, viz, the advent of oil wealth, on the power structure in the emirates. Both factors increased the concentration of central power and decreased popular participation. The study provides a theoretical appraisal of the role and functions of the legislature in developing countries. It examines the constitutional functions namely legislative, political and financial. The study suggests new roles that the legislatures performs in Third World countries. The thesis examines the historical development of the U.A.E. constitutional system. Such development ended In 1971 when the emirates adopted a "Provisional Constitution" to the requirements of the rulers. The study explores the 1971 constitution with particular emphasis on the role of the National Council. It analyses the composition, functions, role and constitutional arrangements of the National Council In the U.A.E. The study provides an analysis of the major political and constitutional cases, In which the FNC was a part, in order to examine the practical working of the constitutional provisions in reality. Finally, the thesis attempts to explain the limitations, Imposed on the National Council, present in the existing constitutional framework and suggests some improvements to the status quo. The coimnon ground throughout the thesis is that a constitution with a democratic tendency does not necessarily establish democratic institutions and that it would be more acceptable in a developing country to introduce evolutionary rather than radical changes to its constitutional system. However, the study clarifies the difficulties of concentration of central power in developing countries.